1999
DOI: 10.1590/s0074-02761999000700014
|View full text |Cite
|
Sign up to set email alerts
|

Features of host cell invasion by different infective forms of Trypanosoma cruzi

Abstract: Through its life cycle from the insect vector to mammalian hosts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…It is interesting to note that the extracts of metacyclic trypomastigotes of either G or CL strains that express distinct repertoires of surface molecules related to their different infectivities are capable of inducing comparable levels of intracellular calcium transient raises in HeLa cells (Ruiz et al 1998), similar to what has been observed here for EA of the same strains. In a previous work, we found that EA from T. cruzi I strains are typically more infective than T. cruzi II parasites (Mortara et al 1999;Fernandes and Mortara 2004). The amastigote surface component(s) that trigger the HeLa cell calcium oscillations observed here have not yet been identified but preliminary evidences indicate that a carbohydrate epitope defined by a monoclonal antibody designated 1D9, abundant in T. cruzi I amastigotes (Barros et al 1997;Mortara et al 1999), could be implicated in this process.…”
Section: Hela Cell Calcium Transients Triggered By T Cruzi Extracellmentioning
confidence: 57%
See 2 more Smart Citations
“…It is interesting to note that the extracts of metacyclic trypomastigotes of either G or CL strains that express distinct repertoires of surface molecules related to their different infectivities are capable of inducing comparable levels of intracellular calcium transient raises in HeLa cells (Ruiz et al 1998), similar to what has been observed here for EA of the same strains. In a previous work, we found that EA from T. cruzi I strains are typically more infective than T. cruzi II parasites (Mortara et al 1999;Fernandes and Mortara 2004). The amastigote surface component(s) that trigger the HeLa cell calcium oscillations observed here have not yet been identified but preliminary evidences indicate that a carbohydrate epitope defined by a monoclonal antibody designated 1D9, abundant in T. cruzi I amastigotes (Barros et al 1997;Mortara et al 1999), could be implicated in this process.…”
Section: Hela Cell Calcium Transients Triggered By T Cruzi Extracellmentioning
confidence: 57%
“…In a previous work, we found that EA from T. cruzi I strains are typically more infective than T. cruzi II parasites (Mortara et al 1999;Fernandes and Mortara 2004). The amastigote surface component(s) that trigger the HeLa cell calcium oscillations observed here have not yet been identified but preliminary evidences indicate that a carbohydrate epitope defined by a monoclonal antibody designated 1D9, abundant in T. cruzi I amastigotes (Barros et al 1997;Mortara et al 1999), could be implicated in this process.…”
Section: Hela Cell Calcium Transients Triggered By T Cruzi Extracellmentioning
confidence: 57%
See 1 more Smart Citation
“…Studies carried out by several groups have shown that involvement of host cell actin with cytochalasins interferes with the internalization of trypomastigote forms into vertebrate cells (Barbosa et al, 1995;Burleigh et al, 1995;Burleigh et al, 1998;Caler et al, 2000;Carvalho et al, 1999;Mortara et al, 1999;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991). In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Both the dividing amastigotes [60] and insect stage epimastigotes [61] are fully capable of establishing infections, and amastigotes are increasingly recognized to share comparable infectivity to trypomastigotes. Amastigote cell entry may follow more stereotyped pattern of cell invasion than the relatively diverse patterns noted between trypomastigotes and their targets.…”
Section: Cell Invasionmentioning
confidence: 99%